Berat Badan Lahir Rendah dengan Kejadian Stunting pada Anak - Adilla Kamilia (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Low Birth Weigth (LBW) is defined as a birth weight of a newborn infant less than 2.500 grams. In addition of being one of the main cause of death on neonatal, infants with LBW are at risk of morbidity and mortality, chronic disease, and stunted growth and development. Based on epidemiological study, infants with LBW have a higher risk of stunting than newborn infants with normal weight. Stunting is a problem of malnutrition that become a concern in the world, especially in developing country like Indonesia. Stunting can cause decreased intelligence, stunted growth and development, decreased body endurance, and low productivity. The long term effects of stunting are decreased cognitive development, learning ability, and productivity. There are several factors besides LBW that can cause stunting, including parental education, low family income, number of family members, and parent’s profession.